Study on the biological effects of ZnO nanosheets on EBL cells - Li, Mei; Ma, Yonghua; Lian, Xiaodi; Lu, Yan; Li, Yuanyuan; Xi, Yao; Sun, Xiaolin (Frontiers in Bioengineering and Biotechnology, 2022)
In this study, the biological effects of ZnO nanosheets were initially investigated using Embryonic bovine lung cells (EBL) cultured in vitro as a model. ZnO nanosheets were prepared by hydrothermal method, and their structure and morphology were characterized, and their effects on EBL cells viability, oxidative stress, cell proliferation, and apoptosis were investigated. The results show that 12.5 μg.ml-1 ZnO nanosheets can cause morphological changes of EBL cells. The toxic effects of ZnO nanosheets on EBL cells were time-dependent. Caspase-3 activity in EBL cells changed under certain conditions with introduction of 25 μg.ml-1 ZnO nanomaterials, EBL cells apoptosis promoted. Under different concentration and time effects, ZnO nanosheets induced the increase of ROS level in EBL cells, indicating that it has oxidative damage effect on cells. The toxic effects of ZnO nanosheets on EBL cells were discussed including concentration effect, time effect and cytotoxic effect, and eventually lead to cell oxidative damage.